Novelties in Phyllanthus (Phyllanthaceae) from the Brazilian Cerrado: new records of the rare species P. allemii - Ribeiro Mendes, Jone Clebson; Figueira, Maurício; Schindler, Bianca; Noronha, Sérgio E.; Fragomeni Simon, Marcelo; Ferreira De Sales, Margareth; Athiê-Souza, Sarah Maria (Phytotaxa, 2022)
Phyllanthus (Phyllanthaceae) is widely distributed within Brazilian phytogeographic domains where 101 species occur, including a number of poorly-known taxa, such as P. allemii, which was until now only known from the type collection. Here we report the rediscovery of P. allemii, which was recently collected during a floristic inventory carried out in the Estação Ecológica Serra Geral do Tocantins, which is located on the border between Bahia and Tocantins states in the Cerrado domain. We provide an updated and detailed morphological description of the species, including plates and field images, as well as a taxonomic key for species of Phyllanthus sect. Phyllanthus subsect. Clausseniani that occur in the Cerrado. We also provide habitat, ecology and distribution data, and, finally, a conservation assessment of this rare species.